The Psychological Distance and Climate Change: A Systematic Review on the Mitigation and Adaptation Behaviors - Maiella, Roberta; La Malva, Pasquale; Marchetti, Daniela; Pomarico, Elena; Di Crosta, Adolfo; Palumbo, Rocco; Cetara, Luca; Di Domenico, Alberto; Verrocchio, Maria Cristina (Frontiers in Psychology, 2020)
Background and Objective: Currently, climate change represents an existential, physical and psychological, threat. Therefore, mitigation and adaptation actions and measures have become increasingly necessary to preserve individual and collective well-being. The psychological distance is one of the main psychological constructs that explains the most concrete or abstract perception of the objects and events surrounding people. The psychological distance is a multidimensional construct, and in accordance with the construal level theory (CLT), temporal, hypothetical, spatial, and social distance are considered the most critical dimensions. This systematic review aims to provide an update of the literature on the role of psychological distance in the commitment to engagement mitigation and adaptation attitudes towards climate change. Method: The review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The data sources were PubMed, PsycInfo, Web of Science, Cochrane, and Scopus databases. Results: Nineteen research articles were identified as eligible and relevant for the final synthesis. Results showed, in general, that individuals have a higher propensity to perform pro-environmental and resilient behaviors against climate change when it is perceived as more proximal and concrete within the construct of psychological distance. However, not all studies show this result. Some studies showed that, despite people considering climate changes as real and tangible, they do not perform mitigation and adaptation behaviors. Other studies showed that people implement these behaviors despite perceiving climate changes as distal and abstract. Conclusions: The current literature shows the existence of a link between psychological distance and pro-environmental and resilient behaviors applied to climate change. For a deeper understanding of the conflicting results that emerged, more studies are needed to investigate the possible presence of further psychological variables involved in the relationship between psychological distance, mitigation, and adaptation in environmental contexts.